Potássio na cultura do Eucalipto: Uma revisão bibliométrica - Cardozo, Leonardo Santos [UNESP] (Universidade Estadual Paulista (Unesp), 2021)
Eucalyptus is a plant that presents fast growth and practicality in relation to the formation of new seedlings, being essential to understand the response to the main nutrients, such as potassium. Potassium acts in the regular functioning of many processes in the plant, with several researches being carried out on the physiological response of the plant. The objective of this work was to demonstrate how the researches on the responses of fertilization with potassium in the eucalyptus crop are found, over the years and active countries. A survey of articles involving this topic had been carried out within the Web of Science database, bringing together and showing the main points to be highlighted in graphs and tables. The surveys found showed different areas of activity, which can add or hinder the cultivation of eucalyptus, mainly in the English language, despite the largest number of surveys being related to agencies, journals or authors affiliated with Brazilian universities. By checking the articles and developing the bibliometric review, it was possible to verify that there are some spaces to which future research can be directed, in order to broaden the understanding of potassium and eucalyptus.

O eucalipto é uma planta que apresenta rápido crescimento e praticidade em relação a formação de novas mudas, sendo imprescindível entender a resposta aos principais nutrientes, como o potássio. O potássio atua no funcionamento regular de muitos processos na planta, sendo realizadas diversas pesquisas sobre a resposta fisiológica da planta. O objetivo deste trabalho foi demonstrar como encontram-se as pesquisas envolta das respostas da adubação com potássio na cultura do eucalipto, ao longo dos anos e países atuantes. Um levantamento dos artigos envolvendo este tema fora realizado dentro do banco de dados da Web of Science, reunindo e demonstrando em gráficos e tabelas os principais pontos a serem evidenciados. As pesquisas encontradas apresentaram diferentes áreas de atuação, que podem agregar ou dificultar o cultivo de eucalipto, se apresentando principalmente no idioma inglês, apesar do maior número de pesquisas estar relacionado a agências, revistas ou autores afiliados a universidades brasileiras. Ao verificar os artigos e desenvolver a revisão bibliométrica, foi possível averiguar que existem alguns espaços aos quais futuras pesquisas podem ser direcionadas, de modo a ampliar a compreensão acerca do potássio e o eucalipto.
Potassium in Eucalyptus culture: A bibliometric review
Keywords: Fertilizing; Eucalyptus; Macronutrients; Adubação; Eucalipto; Macronutriente